Early history of cannabis use in Amsterdam - Jan C. van Ours (Tinbergen Institute, 2025)
Around 50 years ago, the Netherlands decriminalized cannabis for recreational use. This paper uses retrospective data on the ages at which individuals began and ceased cannabis use to reconstruct its prevalence in Amsterdam during the period surrounding the policy change. This approach enables a detailed analysis of the policy's effects. The main conclusion is that the introduction of this policy did not lead to an increase in the prevalence of cannabis use.
Keywords: I12; I18; K42; 330; cannabis use; cannabis policy; age of onset